Analysis of the Factors Causing Delays of Delivery Using the Six Sigma Method (Case Study: Kompindo Wiratama Inc.) - Tirtaningrum, Anggi Putri; Ernawati, Dira (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
The distribution of goods is a very important part of the service or manufacturing industry. One way to maximize the product distribution process is to maintain the quality of service. Service quality is how a company meets or exceeds customer expectations. The problem experienced by Kompindo Wiratama Inc. occurs because of production target discrepancies resulting in delays due several factors. One method that can be used for reducing delivery delays to improve service quality, namely the method of Six Sigma using DMAIC. The concept of DMAIC starts from a stage that define, measure, analyze, improve, and control and at each stage, D-M-A-I-C has objectives and tools different. Obtained an average DPMO value of 33349.08 and an average sigma value of 3.3691. The sigma level that has been achieved is still far from the Decried target, namely 3.4 DPMO and 6 Sigma. The repair phase uses the 5W + 1H analysis technique based on the source of the problem at the fishbone diagram of each CTQ to explain the proposed results of the analysis. After the results of the proposal are given based on the method Six Sigma improvements in handling the four factors of delivery delays will reduce the occurrence of delivery delays in the following months and years. This can improve the quality of service in delivery and maintain customer trust by the company motto, which is "delivery, quality and zero defect”.